Impact of Pancreatic Leaks on Survival Following Pancreaticoduodenectomy - Ausania, Fabio; Cook, Natalie; Jamieson, Neville; Huguet, Emanuel; Jah, Asif; Praseedom, Raaj (JOP. Journal of the Pancreas, 2010)
Context Pancreatic leak following pancreaticoduodenectomy has a major impact on postoperative mortality. However, it is not clear whether pancreatic leaks affect long term survival in patients with pancreatic ductal adenocarcinoma. Objective The aim of this study is to compare the long term outcome in patients who underwent pancreaticoduodenectomy, with and without postoperative pancreatic leak. Patients All 133 patients who underwent a pancreaticoduodenectomy at the HepatoPancreatoBiliary Unit, Addenbrooke’s Hospital, Cambridge, between June 2002 and June 2007 were identified from a prospectively held database. The study was restricted to 47 patients who had a confirmed diagnosis of pancreatic ductal adenocarcinoma. Setting Pancreatic leak was defined as drain fluid amylase more than three times the serum level for more than 3 days post operatively. Main outcome measure Long term survival of patients with and without leaks were compared using Kaplan-Meier curves and significance was measured using the log-rank test. Results Median follow-up was 30.8 months. The median actuarial survival of all ductal adenocarcinoma patients was 19 months. Pancreatic leaks occurred in 9 patients (19.1%). There were no significant differences in the overall survival or presence of recurrence between the two groups. Conclusions Pancreatic leak following pancreaticoduodenectomy does not appear to impact on long-term outcome of patients with pancreatic ductal adenocarcinoma. Image: Kaplan-Meier curve showing no significant difference in the overall survival following pancreaticoduodenectomy between 9 patients with pancreatic leaks and 38 patients without pancreatic leaks.